A critical engagement with theological education in Africa A South African perspective - Knoetze, Johannes J. (Reformed Theology in Africa Series, 2021)
The higher education landscape has arguably become one of the most arduous to traverse. More so in the African context, where a host of variables continiously challenge educators to reflect critically on their philosophies and practices as they engage an ever-changing audience. In this book, a critical engagement with theological education in Africa is offered. As the book originates from South Africa, it is presented as a South African perspective, although contributors are situated accross the African continent and abroad. The common denominator is that all contributers are, in some way or another, invested in theological education in Africa. The main contribution of this collaborative work is to be sought in the insights it offers on four main areas of theological education: A historical and current orientation on theological edcuation in Africa, some paradigm shifts in theological education in Africa, ministerial formation needs versus theological education challenges, and a critical reflection on elective models and methods. The book presents the original and innovative research of scholars for fellow scholars involved in theological higher education as it is grounded in the respective fields of interest of each contributor. It contributes to a better understanding of the complex African theological higher education landscape that is also mindful of post-COVID-19 realities. Methodologically the work draws on a combination of methods, including literature studies, empirical work, and in some cases sectional offerings from doctoral studies, as indicated in the various chapters.